Victorian slum house [videorecording (DVD)] (PBS, 2017)
In this landmark living history series, a Victorian tenement in the heart of London's East End has been painstakingly brought back to life. Host Michael Mosley joins a group of 21st century families as they move in and experience the tough living and working conditions of the Victorian poor.